2019
DOI: 10.1038/s42003-019-0311-z
|View full text |Cite
|
Sign up to set email alerts
|

The atomic structures of shrimp nodaviruses reveal new dimeric spike structures and particle polymorphism

Abstract: Shrimp nodaviruses, including Penaeus vannamei (PvNV) and Macrobrachium rosenbergii nodaviruses (MrNV), cause white-tail disease in shrimps, with high mortality. The viral capsid structure determines viral assembly and host specificity during infections. Here, we show cryo-EM structures of T = 3 and T = 1 PvNV-like particles (PvNV-LPs), crystal structures of the protrusion-domains (P-domains) of PvNV and MrNV, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Examples of suggested duplicated domains that are not discussed in our analysis include the shell (S) and protruding (P) domains of Tombusviridae capsid protein ( Jones et al 1989 ), as well as the P1 and P2 domains of Hepeviridae and Caliciviridae capsid proteins ( Guu et al 2009 ). It is worth pointing out that we also found structural similarity between the Macrobrachium rosenbergii nodavirus capsid P domain and the Black beetle virus capsid S domain (Lsas = 7.7631), both of which have a jelly-roll topology ( Wery et al 1994 ; Chen et al 2019 ), which suggests that some nodaviruses may have undergone a duplication similar to the one suggested by Jones et al (1989) for tombusviruses. Other similar structures that might indicate duplication events but will require further analysis are the Porcine reproductive and respiratory syndrome virus ( Arteriviridae ) nsp1α and nsp1β papain-like cysteine protease domains ( Sun et al 2009 ; Xue et al 2010 ) (Lsas = 6.2778), the coronavirus 3C-like protease and nsp9 ( Sutton et al 2004 ) (Lsas = 13.912), the ssRNA(-) Human respiratory syncytial virus ( Pneumoviridae ) NS1 and matrix protein ( Chatterjee et al 2017 ) (Lsas = 7.4347), the retrovirus capsid N-terminal domain and C-terminal domain (Lsas = 7.0739–8.1531) and the retrovirus reverse transcriptase-ribonuclease H (RT-RNaseH) connection domain, RNaseH domain and integrase (INT) (Lsas INT-RNaseH = 5.7483–6.4967) ( Malik and Eickbush 2001 ), although it has been suggested that the later have independent evolutionary histories ( Koonin et al 2015 ).…”
Section: Discussionsupporting
confidence: 60%
“…Examples of suggested duplicated domains that are not discussed in our analysis include the shell (S) and protruding (P) domains of Tombusviridae capsid protein ( Jones et al 1989 ), as well as the P1 and P2 domains of Hepeviridae and Caliciviridae capsid proteins ( Guu et al 2009 ). It is worth pointing out that we also found structural similarity between the Macrobrachium rosenbergii nodavirus capsid P domain and the Black beetle virus capsid S domain (Lsas = 7.7631), both of which have a jelly-roll topology ( Wery et al 1994 ; Chen et al 2019 ), which suggests that some nodaviruses may have undergone a duplication similar to the one suggested by Jones et al (1989) for tombusviruses. Other similar structures that might indicate duplication events but will require further analysis are the Porcine reproductive and respiratory syndrome virus ( Arteriviridae ) nsp1α and nsp1β papain-like cysteine protease domains ( Sun et al 2009 ; Xue et al 2010 ) (Lsas = 6.2778), the coronavirus 3C-like protease and nsp9 ( Sutton et al 2004 ) (Lsas = 13.912), the ssRNA(-) Human respiratory syncytial virus ( Pneumoviridae ) NS1 and matrix protein ( Chatterjee et al 2017 ) (Lsas = 7.4347), the retrovirus capsid N-terminal domain and C-terminal domain (Lsas = 7.0739–8.1531) and the retrovirus reverse transcriptase-ribonuclease H (RT-RNaseH) connection domain, RNaseH domain and integrase (INT) (Lsas INT-RNaseH = 5.7483–6.4967) ( Malik and Eickbush 2001 ), although it has been suggested that the later have independent evolutionary histories ( Koonin et al 2015 ).…”
Section: Discussionsupporting
confidence: 60%
“…Kueh et al [ 17 ] demonstrated that the Nc produced in Sf 9 cells assembled into homogenous VLPs with a diameter of ~40 nm. Fusion of a small ubiquitin-like modifier (SUMO) protein at the N- or C-terminus of the Nc of a closely related shrimp nodavirus, Penaeus vannamei nodavirus (PvNV), resulted in heterogeneous VLPs [ 32 ]. The additional fusion protein is believed to increase the freedom of dimeric capsomeres, which could result in the formation of heterogeneous VLPs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of a small ubiquitin-like modifier (SUMO) protein at the N- or C-terminus of the Nc of a closely related shrimp nodavirus, Penaeus vannamei nodavirus (PvNV), resulted in heterogeneous VLPs [ 32 ]. The additional fusion protein is believed to increase the freedom of dimeric capsomeres, which could result in the formation of heterogeneous VLPs [ 32 ]. Katsarou et al [ 33 ] showed that the Sf 9-produced enhanced green fluorescent protein (eGFP) fused to the C-terminus of the core protein of hepatitis C virus assembled into heterogeneous VLPs ranging from 30 to 55 nm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of this tetrameric protein is available in Protein Data Bank (PDB; accession code 5YL0) (Fig 1). The conformation of the PvNV P-domain of space group P 2 1 is a dimeric protein (PDB code 5YKZ) and has a parallel shaped model [7] (Fig 2). All three dimeric interfaces in these two proteins have the same interacting residues consisting of Asp256, Val257, Ala293, Phe294, Leu295, Glu296, Gln297, Asn298, Gln300, Pro325, Thr326, Thr328, Thr329, Val330, Ser331, Lys335, Ile364 and Ala366.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies exhibited that the recombinant PvNV CP of full-length 368 amino acids assembles into virus-like particles (VLPs) in the T =3 icosahedral capsids of diameter approximately ∼35-40 nm. The high-resolution 3D reconstructions of the T =3 PvNV VLPs, solved at 3.7 Å resolution, reveals that one CP comprises four regions, including the N-terminal arm (N-arm), the shell domain, the linker and the protrusion domain (P-domain) (residues 250-368) [7,8]. Crystal structures of the PvNV P-domain (PvNVPd) exist in two distinct dimer-dimer conformations of which one possesses one dimer (space group P 2 1 ) and the other has two dimers ( P 2 1 2 1 2 1 ) [7].…”
Section: Introductionmentioning
confidence: 99%